Phosphorus Variations in Volcanic Sequences Reveal the Linkage Between Regional Tectonics and Terrestrial Biota Evolution. (10th August 2022) - Ma, Chao; Tang, Yanjie; Foley, Stephen F.; Ye, Chenyang; Ying, Jifeng; Zhao, Xinmiao; Xiao, Yan; Zhang, Hongfu
Abstract: The Middle‒Late Mesozoic massive volcanism formed a considerable thickness of volcanic‐sedimentary strata in western Liaoning, northern China. Concomitantly, it elevated phosphorus (P) availability for the rapid bloom of the terrestrial Yanliao and Jehol biotas, which developed highly abundant biodiversity and biomass. Hence, systematic tectonic and geochemical analyses of these volcanic‐sedimentary sequences with a significant P fluctuation would advance our understanding of the coevolutionary relationship between terrestrial biotas and regional tectonics. Here, we show that the secular variation of P availability in the Mesozoic volcanic rocks were the immediate results of the changes in volcanic intensity and lithospheric thickness controlled by the geological background of the cratonic destruction resulting from the paleo‐Pacific plate subduction. This study reveals the constraint effect of regional tectonics on the evolution of terrestrial ecosystems through the volcanism and P cycle. Plain Language Summary: The phosphorus (P) is necessary for biotas and mainly comes from volcanics in areas dominated by volcanism closely related to deep‐Earth processes. Thus, the origin of P changes in volcanics can provide key evidence for the intrinsic relations between deep processes and biota evolution. Here, we present tectonic and geochemical analyses for the Mesozoic fossil‐bearing volcanic‐sedimentary strata in northern China. The westward subduction of the paleo‐Pacific plate triggered the crustal thickening and subsequent lithospheric thinning of the East Asia continent. These dynamic processes controlled the volcanic intensity and P variation, resulting in remarkable changes in P availability that led to the rise and fall of terrestrial biotas. Hence, P variations in volcanic sequences reveal the linkage between regional tectonics and biota evolution. This study represents an effort to explore how tectonic processes constrained terrestrial biotas involving multidisciplinary methods. Key Points: The paleo‐Pacific subduction triggered the cratonic destruction and thus controlled the intensity of volcanism in the Middle‒Late Mesozoic The change of lithospheric thickness triggered by the paleo‐Pacific subduction caused the variation of P content in the volcanics Regional tectonics could impact the evolution of terrestrial ecosystems through the volcanism and nutrient P cycle